Pengaruh Perubahan Perilaku Keuangan Generasi Z Di Indonesia Selama Pandemi Covid-19 - Cahyasari, Dyah; Prihatni, Rida (Prodi Manajemen Universitas Pamulang, 2024)
This study aims to examine and analyze the impact of financial literacy and financial technology on financial behavior in students at public and private universities. The population in this study used students in the z generation category at State Universities (PTN) and Private (PTS) throughout Indonesia. The sample used was 124 students, using a purposive sampling technique with several. The type of data used is primary with a questionnaire data collection technique in the form of a google form. This study uses Structural Equation Modeling (SEM) with Partial Least Squares (PLS) 3.2.9 software. to process data. The results of the study partially show that: (1) Digital payments have no effect on financial behavior, (2) Digital payments have a positive effect on financial literacy, (3) Financial literacy has a positive effect on financial behavior, (4) Digital payments have an indirect positive effect on financial behavior through financial literacy as a mediating variable.